1982
DOI: 10.1007/bf02535329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic (Allium sativum linn) on serum lipoproteins and lipoprotein cholesterol levels in albino rats rendered hypercholesteremic by feeding cholesterol

Abstract: The hypocholesteremic activity of garlic was tested by incorporation freeze-dried garlic powder at 0.5, 1.0, 2.0 and 3.0% levels in an atherogenic diet fed to rats. It was observed that 0.5 and 1.0% levels were not effective whereas the other 2 levels were. The group fed 2.0% garlic powder had much lower serum cholesterol level than the one fed 3%. The increased levels of low density lipoproteins (LDL) and LDL-cholesterol in rats fed the atherogenic diet were partly reversed in rats receiving a supplement of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 21 publications
4
30
0
2
Order By: Relevance
“…Our result was agreement with Kamanna VS, et al [13]. experiment which showed that, the increased levels of LDL-C and cholesterol in animals which fed the hypercholestrolemic diet were partly reversed in mice receiving a supplement of garlic powder.…”
Section: Discussionsupporting
confidence: 93%
“…Our result was agreement with Kamanna VS, et al [13]. experiment which showed that, the increased levels of LDL-C and cholesterol in animals which fed the hypercholestrolemic diet were partly reversed in mice receiving a supplement of garlic powder.…”
Section: Discussionsupporting
confidence: 93%
“…Although the mechanism is not clearly defined, its hypo cholestermic (3)(4)(5)(6) and hypolipidemic (4,6,7) actions have been observed. The addition of garlic to a cholesterol diet lowers plasma lipoprotein levels (3), and garlic also reduces the incorporation of 14C-U-acetate and 14C U-sucrose into the lipid fraction of liver and plasma (8).…”
mentioning
confidence: 99%
“…In this respect, 5% garlic powder was more potent (about 19%) than 2.5%. Kamanna et al (1982) and Marta et al (2006) reported a decrease in the serum TC in response to consumption of 2 and 3% garlic powder. They showed that garlic powder made 52 and 33% decrease in serum TC when rats were fed by an atherogenic diet for 8 -9 weeks.…”
Section: Effect Of Garlic Powder On Serum Tgmentioning
confidence: 97%